The Demographic Consequences of the End of Chile S Nitrate Boom, C.1907–1940 - Navarrete-Montalvo, J; Llorca-Jana, M; Rivero-Cantillano, R (Blackwell Publishing Ltd, 2020)
This article deals with the demographic consequences of the end of Chile s nitrate boom following the 1929 crisis. The traditional economic historiography has maintained that this crisis impacted heavily on nitrate production, and that in turn the crisis triggered a permanent exodus from the nitrate districts to other geographical zones. Contrary to this widely held belief, we have shown in this article that: there was no substantial fall in production; there was indeed a fall in nitrate population, but this was limited; this took place in some nitrate areas only; overall, the decline in nitrate population was a short term phenomenon only. The population making a living from nitrate production (or activities directly related to it) did not emigrate in as large numbers as previously thought, since production remained high up to the 1960s. © 2019 Society for Latin American Studies